10 Minutes 38 Seconds in This Strange World - Shafak, Elif (Canada Viking, 2019)
'In the first minute following her death, Tequila Leila's consciousness began to ebb, slowly and steadily, like a tide receding from the shore. Her brain cells, having run out of blood, were now completely deprived of oxygen. But they did not shut down. Not right away...' Our brains stay active for ten minutes after our heart stops beating. For Tequila Leila, each minute brings with it a new memory - growing up with her father and his two wives in a grand old house in a quiet Turkish town; watching the women gossip and wax their legs while the men went to mosque; sneaking cigarettes and Western magazines on her way home from school; running away to Istanbul to escape an unwelcome marriage; falling in love with a student who seeks shelter from a riot in the brothel where she works. Most importantly, each memory reminds Leila of the five friends she met along the way - the friends who are now desperately trying to find her